Theoretical Calculations For Sputtering Yield of Iron Bombarding by (H, D, T, He) Ions - Jawad, Enas A .; Jassim, Mustafa K.; Tawfeek, Huda M . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Extended calculations for  sputtering yield   through bombed Iron â€“ target   by ( H,D ,T ,He )  ions plasma are accomplished .The calculations include changing the  input    parameters  :    the energy  of ( H,D ,T ,He ) ions plasma, the hit target angle of Iron, change  atomic   mass  of incident ion. The program TRIM is used to accomplish these calculations. The results     show   that   sputtering   yield is   directly   dependent   on   these parameters. It can   change the incident angle of ( H,D ,T ,He ) ions   and energy  lead   to  a  significant   change   in  sputtering   yield     on    the  other hand.   The sputtering yields are highly affected by changing of incident ion mass at fixed other target parameters. It can be shown from calculation that whenever increased incident ion mass increase sputtering yield, increases  with   incident  ions energy   and  then   begins  to  decline, sputtering  will  not  occur ,  at   incident  ion   energies below the  threshold  energy . In this study we found that the sputtering yield depends    on incidence angle, incident ions energy and atomic mass of target.